Shaping the biology of citrus: I. Genomic determinants of evolution - González-Ibeas, Daniel; Ibanez, Victoria; Pérez-Román, Estela; Borredá, Carles; Terol, Javier; Talón, Manuel (Wiley Online Library, 2021)
We performed genomic analyses on wild species of the genus Citrus to identify major determinants of evolution. The most notable effect occurred on the pathogen-defense genes, as observed in many other plant genera. The gene space was also characterized by changes in gene families intimately related to relevant biochemical properties of citrus fruit, such as pectin modifying enzymes, HDR (4-hydroxy-3-methylbut-2-enyl diphosphate reductase) genes, and O-methyltransferases. Citrus fruits are highly abundant on pectins and secondary metabolites such as terpenoids and flavonoids, the targets of these families. Other gene types under positive selection, expanded through tandem duplications and retained as triplets from whole genome duplications, codified for purple acid phosphatases and MATE-efflux proteins. Although speciation has not been especially rapid in the genus, analyses of selective pressure at the codon level revealed that the extant species evolved from the ancestral citrus radiation show signatures of pervasive adaptive evolution and is therefore potentially responsible for the vast phenotypic differences observed among current species. by changes in gene families intimately related to relevant biochemical properties of citrus fruit, such as pectin modifying enzymes, HDR (4-hydroxy-3-methylbut-2- enyl diphosphate reductase) genes, and O-methyltransferases. Citrus fruits are highly abundant on pectins and secondary metabolites such as terpenoids and flavonoids, the targets of these families. Other gene types under positive selection, expanded through tandem duplications and retained as triplets from whole genome duplications, codified for purple acid phosphatases and MATE-efflux proteins. Although speciation has not been especially rapid in the genus, analyses of selective pressure at the codon level revealed that the extant species evolved from the ancestral citrus radiation show signatures of pervasive adaptive evolution and is therefore potentially responsible for the vast phenotypic differences observed among current species.